Positive Criminology and Rethinking the Response to Adolescent Addiction: Evidence on the Role of Social Support, Religiosity, and Service to Others - Johnson, Byro R.; Lee, Matthew T.; Pagano, Maria E.; Post, Stephen G. (International Journal of Criminology and Sociology, 2016)
Adolescent addiction has emerged as a major public health problem. The greatest increase in alcohol and other drug use disorders can be found among youth. Concurrently, technological advances in policing coupled with aggressive prosecuting and sentencing practices have contributed to the growth of America’s correctional system. The assertive response of policing, courts, and corrections, however, have not prevented the dramatic rise of adolescent addiction. Unfortunately, there is no national data tracking addicted youth in the criminal justice system to evaluate what works when it comes to youth with addiction. This article reviews justice system responses to adolescent offenders with addiction, and promising approaches engaging juveniles in programmatic components of Alcoholics Anonymous (AA). This study highlights the role of spirituality, service to others, and social support in maintaining sobriety, reducing arrests, and lowering recidivism for adolescents court-referred to treatment. Recommendations for improving the response to adolescent offenders with addiction are offered.